8x(x-5)=4x-10+3x-30

Simple and best practice solution for 8x(x-5)=4x-10+3x-30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x(x-5)=4x-10+3x-30 equation:


Simplifying
8x(x + -5) = 4x + -10 + 3x + -30

Reorder the terms:
8x(-5 + x) = 4x + -10 + 3x + -30
(-5 * 8x + x * 8x) = 4x + -10 + 3x + -30
(-40x + 8x2) = 4x + -10 + 3x + -30

Reorder the terms:
-40x + 8x2 = -10 + -30 + 4x + 3x

Combine like terms: -10 + -30 = -40
-40x + 8x2 = -40 + 4x + 3x

Combine like terms: 4x + 3x = 7x
-40x + 8x2 = -40 + 7x

Solving
-40x + 8x2 = -40 + 7x

Solving for variable 'x'.

Reorder the terms:
40 + -40x + -7x + 8x2 = -40 + 7x + 40 + -7x

Combine like terms: -40x + -7x = -47x
40 + -47x + 8x2 = -40 + 7x + 40 + -7x

Reorder the terms:
40 + -47x + 8x2 = -40 + 40 + 7x + -7x

Combine like terms: -40 + 40 = 0
40 + -47x + 8x2 = 0 + 7x + -7x
40 + -47x + 8x2 = 7x + -7x

Combine like terms: 7x + -7x = 0
40 + -47x + 8x2 = 0

Begin completing the square.  Divide all terms by
8 the coefficient of the squared term: 

Divide each side by '8'.
5 + -5.875x + x2 = 0

Move the constant term to the right:

Add '-5' to each side of the equation.
5 + -5.875x + -5 + x2 = 0 + -5

Reorder the terms:
5 + -5 + -5.875x + x2 = 0 + -5

Combine like terms: 5 + -5 = 0
0 + -5.875x + x2 = 0 + -5
-5.875x + x2 = 0 + -5

Combine like terms: 0 + -5 = -5
-5.875x + x2 = -5

The x term is -5.875x.  Take half its coefficient (-2.9375).
Square it (8.62890625) and add it to both sides.

Add '8.62890625' to each side of the equation.
-5.875x + 8.62890625 + x2 = -5 + 8.62890625

Reorder the terms:
8.62890625 + -5.875x + x2 = -5 + 8.62890625

Combine like terms: -5 + 8.62890625 = 3.62890625
8.62890625 + -5.875x + x2 = 3.62890625

Factor a perfect square on the left side:
(x + -2.9375)(x + -2.9375) = 3.62890625

Calculate the square root of the right side: 1.904968832

Break this problem into two subproblems by setting 
(x + -2.9375) equal to 1.904968832 and -1.904968832.

Subproblem 1

x + -2.9375 = 1.904968832 Simplifying x + -2.9375 = 1.904968832 Reorder the terms: -2.9375 + x = 1.904968832 Solving -2.9375 + x = 1.904968832 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.9375' to each side of the equation. -2.9375 + 2.9375 + x = 1.904968832 + 2.9375 Combine like terms: -2.9375 + 2.9375 = 0.0000 0.0000 + x = 1.904968832 + 2.9375 x = 1.904968832 + 2.9375 Combine like terms: 1.904968832 + 2.9375 = 4.842468832 x = 4.842468832 Simplifying x = 4.842468832

Subproblem 2

x + -2.9375 = -1.904968832 Simplifying x + -2.9375 = -1.904968832 Reorder the terms: -2.9375 + x = -1.904968832 Solving -2.9375 + x = -1.904968832 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.9375' to each side of the equation. -2.9375 + 2.9375 + x = -1.904968832 + 2.9375 Combine like terms: -2.9375 + 2.9375 = 0.0000 0.0000 + x = -1.904968832 + 2.9375 x = -1.904968832 + 2.9375 Combine like terms: -1.904968832 + 2.9375 = 1.032531168 x = 1.032531168 Simplifying x = 1.032531168

Solution

The solution to the problem is based on the solutions from the subproblems. x = {4.842468832, 1.032531168}

See similar equations:

| 12x+y=-60 | | -5(7-x+5x)= | | -5n+6=-35n-42-6n | | 16=[2w+w-1] | | 7y+27=6y-3 | | 3(60)-3x=99 | | 50+3x=14 | | 9a-9.4=8a+4.6 | | -6+x=19 | | -2-2x-5x=-37 | | 8(3-2)=104 | | (y^2-7y-5)-(-3y^2+3y-4)= | | 2(5r+45)=20(2r-24) | | 5n+7+n=3n-2+4n(2n+1) | | t=4+3x | | -10-(-5x)=5x | | 3x+11-x=8+4x-5 | | -4.4+6.2=5x-2.9-4x | | x=4+3t | | 2+0.5x=3-5x | | 7-3u^2=1 | | 50+3x=4 | | x+65+57=90 | | 7(9n-4)= | | 5=12(2cosx+sinx) | | 4x+9x-3x=37+3 | | Y=6x^2-13x-8 | | 2c+4d=4 | | 7x+2(x-14)=80 | | 6.2+x=3.8 | | (6x^3+8x+3)-(5x^2+3x+10)= | | 10j+1=-2j |

Equations solver categories